1992
DOI: 10.1291/hypres.15.45
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Dietary Factors to Cardiovascular Diseases among Japanese in Okinawa and Japanese Immigrants, Originally from Okinawa, in Brazil.

Abstract: To investigate the relationship of dietary factors to cardiovascular diseases, we conducted a study of 234 middle-aged Japanese men and women in Okinawa (JJ), and 160 Japanese immigrants of similar age, originally from Okinawa, in Brazil (JB). JB showed double the prevalence (%) of ST-T changes in the electrocardiogram (ECG) (JJ: M3.4, F4.4, JB: M8.3, F10.1) and of hypertension (HT) (JJ: M15.9, F18.4; JB: M32.8, F36.4, p < 0.05) when this was assessed on BP> 160195 and/or the taking of antihypertensive medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 50 publications
(52 reference statements)
2
24
0
Order By: Relevance
“…A remarkable difference of the dietary pattern between Japan and Brazil has been reported. 15,16 Mizushima et al confirmed a lower frequency of fish intake by JapaneseBrazilians (immigrants from Okinawa) compared with Japanese living in Okinawa. 15,16 Furthermore, a lower value of n-3 polyunsaturated fatty acids (PUFA) in plasma in Japanese-Brazilians has been shown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A remarkable difference of the dietary pattern between Japan and Brazil has been reported. 15,16 Mizushima et al confirmed a lower frequency of fish intake by JapaneseBrazilians (immigrants from Okinawa) compared with Japanese living in Okinawa. 15,16 Furthermore, a lower value of n-3 polyunsaturated fatty acids (PUFA) in plasma in Japanese-Brazilians has been shown.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Mizushima et al confirmed a lower frequency of fish intake by JapaneseBrazilians (immigrants from Okinawa) compared with Japanese living in Okinawa. 15,16 Furthermore, a lower value of n-3 polyunsaturated fatty acids (PUFA) in plasma in Japanese-Brazilians has been shown. 16 In a Rotterdam study, fish consumption has been inversely related to the incidence of dementia, especially AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main source of zinc is meat. Okinawians have the highest meat intake in Japan, but they have only half meat intake frequency Brazilian immigrants [14]. The Japanese in general have a relatively high intake of copper in the range of 1.3 mg/day (18) to 1.6 mg/day [19].…”
Section: Discussionmentioning
confidence: 99%
“…Japanese from Okinawa have half the IHD mortality of all Japan. However, first-generation Japanese who emigrated from Japan (originally from Okinawa) to Brazil have almost fourfold increased IHD mortality rate [13,14]. The data are summarised in Table I. The aim of the present study was to compare the leucocyte and plasma copper and zinc in Japanese from Okinawa with Japanese immigrants (originally from Okinawa) living in two cities in Brazil: Sao Paulo and Campo Grande.…”
Section: Introduction Copper Zinc and Atherosclerosis?mentioning
confidence: 99%